Lyrics of Kawih Tanah Sunda by Koko Koswara as a Media for Learning Cultural Literacy for Students in Junior High School - Muliawati, Ema Siti; Maryanti, Rina (Bumi Publikasi Nusantara, 2022)
Indonesia has been carrying out online learning for more than 2 years in an effort to break the chain of transmission of Covid-19. With the community service program, it is hoped that there will be an increase in student interest in learning and make it easier for educators and parents to carry out online learning activities. Included in the learning of Kawih